Fibrolase: Trials and Tribulations - Markland, Francis S. (MDPI, 2010)
Fibrolase is the fibrinolytic enzyme isolated from Agkistrodon contortrix contortrix (southern copperhead snake) venom. The enzyme was purified by a three-step HPLC procedure and was shown to be homogeneous by standard criteria including reverse phase HPLC, molecular sieve chromatography and SDS-PAGE. The purified enzyme is a zinc metalloproteinase containing one mole of zinc. It is composed of 203 amino acids with a blocked amino-terminus due to cyclization of the terminal Gln residue. Fibrolase shares a significant degree of homology with enzymes of the reprolysin sub-family of metalloproteinases including an active site homology of close to 100%; it is rapidly inhibited by chelating agents such as EDTA, and by alpha2-macroglobulin (α2Μ). The enzyme is a direct-acting thrombolytic agent and does not rely on plasminogen for clot dissolution. Fibrolase rapidly cleaves the A(α)-chain of fibrinogen and the B(β)-chain at a slower rate; it has no activity on the γ-chain. The enzyme exhibits the same specificity with fibrin, cleaving the α-chain more rapidly than the β-chain. Fibrolase was shown to have very effective thrombolytic activity in a reoccluding carotid arterial thrombosis model in the canine. A recombinant version of the enzyme was made in yeast by Amgen, Inc. (Thousand Oaks, CA, USA) and called alfimeprase. Alfimeprase is identical to fibrolase except for a two amino acid truncation at the amino-terminus and the insertion of a new amino-terminal amino acid in the truncated protein; these changes lead to a more stable enzyme for prolonged storage. Alfimeprase was taken into clinical trials by Nuvelo, Inc. (San Carlos, CA), which licensed the enzyme from Amgen. Alfimeprase was successful in Phase I and II clinical trials for peripheral arterial occlusion (PAO) and central venous access device (CVAD) occlusion. However, in Phase III trials alfimeprase did not meet the expected end points in either PAO or CVAD occlusion and in a Phaase II stroke trial, and Nuvelo dropped further development in 2008.